Essential oil composition, in vivo antioxidant, and antimicrobial activities of Pimpinella pruatjan from West Java, Indonesia - Nurcahyanti, Agustina Dwi Retno; Nasser, Issam Jumaa; Sporer, Frank; Wetterauer, Bernhard; Kadarso, Ireng D.; Wink, Michael (The natural products journal, 2018)
Background: The root of the Indonesian Pimpinella pruatjan Molk. has been mainly used - as an aphrodisiac and for the treatment of Erectile Dysfunction (ED)....
Gesehen am 25.03.2020